Pengembangan soal literasi numerasi berbantuan quizizz dengan menggunakan konteks sosial budaya kota tebing tinggi - Asyari, Annisa; Saputra, Eri; Wulandari, Wulandari; Nuraina, Nuraina; Listiana, Yeni (IKIP Siliwangi, 2024)
The study was undermined by student’s numeracy literacy skills which were still low with an average score of 27. Students were not accustomed to do numeracy literacy questions because there was no valid collection of numeracy literacy questions. So, this research aims to provide and evaluate the viability, usefulness, and efficacy of numeracy literacy questions based on quizizz by applying Tebing Tinggi’s sociocultural context. The ADDIE development model comprising the phases of analysis, design, development, implementation, and evaluation was employed in this study. The subjects of this research were class VIII student at SMP Ir. H. Djuanda Tebing Tinggi. Based on the findings of research and development, it is possible to see that the product of numeracy literacy questions on quizizz which was developed using comparative material that is feasible and practical but is not effectively used by student at SMP Ir. H. Djuanda Tebing Tinggi.